Decoupling transformation for piezoelectric-piezomagnetic fibrous composites with imperfect interfaces - Kuo, Hsin-Yi; Chen, Chin-Yuan (My University, 2015)
We study the effective magnetoelectricity of piezoelectric-piezomagnetic fibrous composites with imperfect interfaces subjected to anti-plane shear deformation coupled to in-plane electromagnetic fields. Two kinds of imperfect interfaces, mechanically stiff and highly electromagnetic conducting interfaces, and mechanically compliant and weakly electromagnetic conducting interfaces, are considered for the phenomenon of contact resistance between the constituents. The decoupling transformation approach previously used in composite media with perfect interfaces is extended to the current configuration. The predicted macroscopic behaviors are in good agreement with the known solutions. It is observed that moduli of the composite with imperfect contacts do not fulfill the compatibility conditions L*La-1Lb - LbLa-1L* = 0, which was supposed to be microstructure independent connections for the two-phase heterogeneous media. Finally, we use the two-level recursive scheme to show the equivalence between the imperfect interfaces and an infinity thin homogeneous interface layer. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Effective property; Piezoelectric-piezomagnetic fibrous composite; Imperfect interface; Decoupling transformation